TRANSLANGUAGING AS MOTIVATION FOR EMBRACING MINORITY LANGUAGES - Pethias Siame; Kelvin Mambwe; Djalilova Malika Shuxratovna; Kennedy Njenje Kangwa (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The study problematises language-in-education policies in Zambia which do not favour minority languages. Due to a multiplicity of languages in Zambia, seven Regional Official Languages (ROLs) were arrived at by the government. These are Bemba, Lozi, Tonga, Nyanja, Kaonde, Lunda, and Luvale. Bemba was assigned to be used for initial literacy in the Northern, Muchinga and Copperbelt regions of Zambia where Lungu, Mambwe and Namwanga languages are spoken. However, the language-in-education policy of 2014 hardly takes into account the presence of minority languages which are often ground level languages for child play. Using a qualitative approach, elicitation and document analysis methods, this paper accounts for the similarities in Bemba, Lungu, Mambwe, and Namwanga languages in order to demonstrate the potential need for translanguaging as a pedagogic resource in education. The paper is undergirded by translanguaging, a key theoretical concept which appreciates the role of multiple languages in education set-ups. The results show that the four languages are found in the same region and are often used as amalgams by speakers in different social spaces of communication due to the multilingual nature of the area. The results also reveal that due to a wide array of similarities at the phonological and morphological levels of the four languages, translanguaging can be a useful pedagogic resource during initial literacy, primary, secondary, and tertiary education levels. Therefore, embracing translanguaging as a resource in language-in-education policies can enhance multilingualism, language learning, improved communication, and the preservation of linguistic heritage in Zambia particularly for minority languages.